2009
DOI: 10.1016/j.juro.2008.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Robot Assisted Laparoscopic Partial Nephrectomy: A Viable and Safe Option in Children

Abstract: Our initial experience shows the safety and feasibility of robot assisted laparoscopic partial nephrectomy in children. Operative time decreases with experience. The enhanced visualization and dexterity of a robotic system potentially offer improved efficiency and safety over standard laparoscopy. Robot assisted laparoscopy is an option for partial nephrectomy and may become the minimally invasive treatment of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 12 publications
1
44
0
2
Order By: Relevance
“…We began performing laparoscopic heminephrectomy in 2005, and surgical time was good compared to open surgery at that time. Our surgical time is similar to that of other series (Table 3), and is better than when using robot-assisted surgery [18].…”
Section: Discussionsupporting
confidence: 85%
“…We began performing laparoscopic heminephrectomy in 2005, and surgical time was good compared to open surgery at that time. Our surgical time is similar to that of other series (Table 3), and is better than when using robot-assisted surgery [18].…”
Section: Discussionsupporting
confidence: 85%
“…Partial nephrectomy can be used in the management of renal duplication anomalies, such as a nonfunctioning upper (or lower) pole segment with ureterocele or ectopic ureter, cystic malformation of the upper pole kidney, and a nonfunctioning refluxing lower pole kidney. 46 Surgical management consists of identification of the upper and lower pole vessels and ureter. Children with a duplication anomaly will have a clear vascular and anatomic plane between the upper and lower pole kidney.…”
Section: Partial Nephrectomy (Heminephroureterectomy)mentioning
confidence: 99%
“…[11] Because children with a duplication anomaly present with a clear vascular and anatomic plane between the upper and lower pole of the kidney, robotic-assisted HNU (RAHNU) is a good choice for these children.…”
Section: Heminephroureterectomy (Nephron-sparing Surgery)mentioning
confidence: 99%
“…In two patients, the procedure was converted to an open operation. Recently, Lee et al [11] reported on the safety and feasibility of RAHNU in children. In their series, RAHNU was completed successfully in nine cases with a mean operative time of 275 minutes, and an estimated blood loss of 49 mL.…”
Section: Heminephroureterectomy (Nephron-sparing Surgery)mentioning
confidence: 99%